Mitochondrial protein dysfunction in pathogenesis of neurological diseases - Wang, Liang; Yang, Ziyun; He, Xiumei; Pu, Shiming; Yang, Cheng; Wu, Qiong; Zhou, Zuping; Cen, Xiaobo; Zhao, Hongxia (Frontiers in Molecular Neuroscience, 2022)
Mitochondria are essential organelles for neuronal function and cell survival. Besides the well-known bioenergetics, additional mitochondrial roles in calcium signaling, lipid biogenesis, regulation of reactive oxygen species and apoptosis are pivotal in diverse cellular processes, such as synaptic plasticity and microglial activation. The mitochondrial proteome encompasses about 1500 proteins encoded by both the nuclear DNA and the maternally inherited mitochondrial DNA. Mutations in the nuclear or mitochondrial genome genes, or combinations of both, can result in mitochondrial protein deficiencies and mitochondrial malfunction. Therefore, mitochondrial quality control by proteins involved in various surveillance mechanisms is critical for neuronal integrity and viability. Abnormal proteins involved in mitochondrial bioenergetics, dynamics, mitophagy, import machinery, and mitochondrial DNA maintenance have been linked to the pathogenesis of a number of neurological diseases. The goal of this review is to give an overview of these pathways and to summarize the interconnections between mitochondrial protein dysfunction and neurological diseases.